Analisis Penerapan Syariah Pembiayaan Rahn Emas - Eka Widiyani; Siti Afidatul Khotjah (Universitas Bangka Belitung, 2020)
Abstract: This study aims to determine whether the principles of sharia are applied and the financing of gold in the Sharia Pawnshop Mertoyudan Branch Office, whether it is in accordance with sharia principles in accordance with the established rules. This study uses qualitative methods using primary data, namely through direct interviews with the parties concerned and observation. In addition to primary data as well as secondary data taken through books, journals, internet, and previous research, the data obtained are not numbers but information related to this research. The result of this research is that the gold rahn financing in sharia pawnshops uses a combination of two contracts, namely the rahn contract and the ijarah contract. The ijarah rates set are based on the size of the loan. The legal basis used is based on Al-Qura'an Surat Al-Baqarah ([2]: 283), Bukhari Muslim's Hadith, and the Fatwa of the National Sharia Council of the Indonesian Ulema Council No.25 / DSN-MUI / III / 2002. The auction system implemented in the Sharia Pawnshop Mertoyudan Branch Office is in accordance with the Fatwa of the National Sharia Council of the Indonesian Ulema Council No.25 / DSN-MUI / III / 2002 regarding rahn, but the status of gold rahn collateral is still questionable whether it is in accordance with sharia principles or not yet because the Mertoyudan Branch Office Sharia Pawnshop doesn't pay attention to the status of the collateral. Keywords: Gold Rahn, Sharia Principles, Financing.